Clinical, histological and genetic characterisation of patients with tubular aggregate myopathy caused by mutations in STIM1. Issue 12 (17th October 2014) - Böhm, Johann; Chevessier, Frédéric; Koch, Catherine; Peche, G Arielle; Mora, Marina; Morandi, Lucia; Pasanisi, Barbara; Moroni, Isabella; Tasca, Giorgio; Fattori, Fabiana; Ricci, Enzo; Pénisson-Besnier, Isabelle; et al.
Abstract : Background: Tubular aggregate myopathies (TAMs) are muscle disorders characterised by abnormal accumulations of densely packed single-walled or double-walled membrane tubules in muscle fibres. Recently, STIM1, encoding a major calcium sensor of the endoplasmic reticulum, was identified as a TAM gene. Methods: The present study aims to define the clinical, histological and ultrastructural phenotype of tubular aggregate myopathy and to assess the STIM1 mutation spectrum. Results: We describe six new TAM families harbouring one known and four novel STIM1 mutations. All identified mutations are heterozygous missense mutations affecting highly conserved amino acids in the calcium-binding EF-hand domains, demonstrating the presence of a mutation hot spot for TAM. We show that the mutations induce constitutive STIM1 clustering, strongly suggesting that calcium sensing and consequently calcium homoeostasis is impaired. Histological and ultrastructural analyses define a common picture with tubular aggregates labelled with Gomori trichrome and Nicotinamide adenine dinucleotide (NADH) tetrazolium reductase, substantiating their endoplasmic reticulum origin. The aggregates were observed in both fibre types and were often accompanied by nuclear internalisation and fibre size variability. The phenotypical spectrum ranged from childhood onset progressive muscle weakness and elevated creatine kinase levels to adult-onset myalgia without muscle weakness and normal CK levels. Conclusions: The present study expands the phenotypical spectrum of STIM1 -related tubular aggregate myopathy. STIM1 should therefore be considered for patients with tubular aggregate myopathies involving either muscle weakness or myalgia as the first and predominant clinical sign.